Neuroevolution under unimodal error landscapes - Jagusch, Jan-Benedikt (2018)
Jagusch, J-B., Gonçalves, I., & Castelli, M. (2018). Neuroevolution under unimodal error landscapes: An exploration of the semantic learning machine algorithm. In GECCO 2018 Companion - Proceedings of the 2018 Genetic and Evolutionary Computation Conference Companion (pp. 159-160). Association for Computing Machinery, Inc. DOI: 10.1145/3205651.3205778